Synchrotron-Based Infrared Microanalysis of Biological Redox Processes under Electrochemical Control - Ash, Philip A. (Anal Chem, 2016)
[Image: see text] We describe a method for addressing redox enzymes adsorbed on a carbon electrode using synchrotron infrared microspectroscopy combined with protein film electrochemistry. Redox enzymes have high turnover frequencies, typically 10–1000 s(–1), and therefore, fast experimental triggers are needed in order to study subturnover kinetics and identify the involvement of transient species important to their catalytic mechanism. In an electrochemical experiment, this equates to the use of microelectrodes to lower the electrochemical cell constant and enable changes in potential to be applied very rapidly. We use a biological cofactor, flavin mononucleotide, to demonstrate the power of synchrotron infrared microspectroscopy relative to conventional infrared methods and show that vibrational spectra with good signal-to-noise ratios can be collected for adsorbed species with low surface coverages on microelectrodes with a geometric area of 25 × 25 μm(2). We then demonstrate the applicability of synchrotron infrared microspectroscopy to adsorbed proteins by reporting potential-induced changes in the flavin mononucleotide active site of a flavoenzyme. The method we describe will allow time-resolved spectroscopic studies of chemical and structural changes at redox sites within a variety of proteins under precise electrochemical control.